PROSPECTS FOR REGIONAL FISH FARMING IN THE REPUBLIC OF KAZAKHSTAN - Okumbekova, M. B.; Aidaraliyeva, A. A.; Bazarova, B. T. (Ғылым және білім=Наука и образование=Science and education № 1-3 (70), 2023)
Ability to meet the demands of the population in fish and fish products and its food security is one of the most acute problems in the Republic of Kazakhstan.Objective – the current state of the fisheries of the Republic of Kazakhstan was studied and proposals for the development of the fisheries in the West Kazakhstan region were made. Methods – statistical methods of data analysis were used to study the state of the fisheries of the Republic of Kazakhstan, and exclusively the catch of fish and other aquatic animals, as well as the dependency of the physical volume of fish farming production from the total amount of products made. Results - the study discusses topical issues of the production capacity of fisheries and fish canneries, by types and volumes of output products, economic indicators, as well as by enterprises engaged in the purchase and sale of fish products, wholesale and retail trade, problems of marketing research in the field of fish products production and safety. Conclusions - creation of the laboratories and fish breeding in autonomous facilities will allow development of the innovative technologies for rearing, preservation, and replenishment of fish resources in water bodies of the region, will provide a training base for the future specialists training, will create prerequisites for preservation and multiplication of fish resources in Kazakhstan, will improve the food security of the country, and will resolve the key problems of the fish industry development. Artificial fish farming involves interfering with the development of organisms to increase their production, such as regular restocking, feeding, protection from predators, etc. Выращивание рыб и других водных животных является наиболее востребованным трендом в вопросах, как обеспечения пищевой безопасности, так и снятия антропогенной нагрузки с естественных водоемов в результате чрезмерной их эксплуатации. Цель – исследовано состояние рыбного хозяйства Республики Казахстан и дана оценка экономического потенциала развития отрасли рыбного хозяйства Западно-Казахстанской области. Методы - на основе статистических данных проанализировано состояние рыбного хозяйства Республики Казахстан, непосредственно по улову рыбы и других водных животных, а также зависимость физического объема выпущенной продукции рыбоводства от общего количества произведенной продукции. Результаты- в исследовании обсуждаются актуальные вопросы и современные пути выращивания рыбы в установках замкнутого водоснабжения, а также решение проблем развития аквакультуры путем создания лаборатории в ЗКО, так как регион является наиболее подходящим для осуществления концепции нового типа эксплуатации внутренних водоёмов, развитию пастбищного рыбоводства и аквакультуры, по природно-климатическим особенностям, обилию водоёмов разного типа, наличию мощного научного потенциала и ценных результатов многолетних наблюдений за ихтиофауной.
Keywords: научный журнал; периодическое издание; отечественное издание; экономика АПК; рыбное хозяйство; fish resources; innovative technologies; инновационные технологии; ихтиофауна